Hospitalization risk of the 2009 H1N1 pandemic cases in Hong Kong - Wang, Xi-Ling (BioMed Central, 2014)
BACKGROUND: Reliable assessment for the severity of the 2009 H1N1 pandemic influenza is critical for evaluation of vaccination strategies for future pandemics. This study aims to estimate the age-specific hospitalization risks of the 2009 pandemic cases during the first wave in Hong Kong, by combining the findings from the serology and disease burden studies. METHODS: Excess hospitalization rates associated with the pandemic H1N1 were estimated from Poisson regression models fitted to weekly total numbers of non-accidental hospitalization from 2005 to 2010. Age-specific infection-hospitalization risks were calculated as excess hospitalization rates divided by the attack rates in the corresponding age group, which were estimated from serology studies previously conducted in Hong Kong. RESULTS: Excess hospitalization rate associated with pandemic H1N1 was highest in the 0–4 age group (881.3 per 100,000 population), followed by the 5–14, 60+, 15–29, 50–59, 30–39 and 40–49 age groups. The hospitalization risk of the infected cases (i.e. infection-hospitalization risk) was found highest in the 60+ age group and lowest in the 15–29 age group, with the estimates of 17.5% and 0.7%, respectively. CONCLUSIONS: People aged 60 or over had a relatively high infection-hospitalization risk during the first wave of the 2009 H1N1 pandemic, despite of a low attack rate in this age group. The findings support the policy of listing older people as the priority group for pandemic vaccination.